Assessment of MIR3142HG genetic polymorphisms and the susceptibility of lumbar disc herniation in the Chinese population - Qi Dong; Guoxia Ren; Dingjun Hao (Scientific Reports)
Abstract Lumbar disc herniation (LDH) is a common degenerative disease of the lumbar spine, which is related to host genetic factors. Our study aimed to explore the association between MIR3142HG polymorphisms and LDH susceptibility. Six SNPs in MIR3142HG from 504 LDH patients and 500 healthy individuals were genotyped by the Agena MassARRAY platform. The relationship between SNPs and LDH susceptibility was evaluated with logistic regression analysis by calculating odds ratios (ORs) and 95% confidence intervals (CIs). The interactions between SNP and SNP were analyzed using the multifactor dimensionality reduction (MDR) method. Our study showed that rs7727115 was related to a decreased susceptibility to LDH. Rs2961920 and rs58747524 were significantly associated with an increased risk of LDH. Stratified analysis showed that rs7727115 reduced the risk of LDH in patients aged > 49 years. Rs17057846, rs2961920, and rs58747524 had a risk-increasing influence on patients aged > 49 years and women. Besides, rs7727115 decreased susceptibility in cases of disc prolapse, while rs2961920 and rs58747524 increased the risk. Rs2431689 increased susceptibility in patients with a single hernia, and rs58747524 correlated with an increased risk in cases of multiple hernias. Moreover, MDR analysis indicated that the combination of rs1582417, rs2431689, rs7727115, rs17057846, rs2961920, and rs58747524 was the best predictive model for LDH. Our study showed that MIR3142HG polymorphisms were significantly associated with LDH risk, which suggests that MIR3142HG polymorphisms play some potential roles in diagnosing LDH.